The neo-pentecostal anthesis:: Reverendo Caio Fábio and the movement of resistence to brazilian neo-pentecostalism. (1991 – 2018) (Ágora Journal, 2023)
On September 23, 1995, the Associação Evangélica Brasileira (AEVB) issued a manifesto opposing the “anti-evangelical” practices of the Igreja Universal do Reino de Deus (IURD) and their leader. This document “disallowed” the IURD to speak out on behalf of all evangelicals. Nowadays, there is still an internal movement that is – although far from representing the largest portion – resistant and antithetical, for example, to Bolsonarism and its allies engaged in the dome of the Brazilian evangelical caucus. We seek to analyze this movement in opposition to neo-Pentecostalism, and highlight that, contrary to what one might slightly conclude, the neo-Pentecostal movement encountered resistance already in its first representations in Brazil. We will deal with the figure of the Reverend Caio Fábio d'Araújo Filho as a globalizing subject of these antithetical postures.
Keywords: Neo-pentecostalis; Antithetical; Caio Fábio; AEVB